Enhancing Web Learning System Using Multimedia and Regression Algorithm - Mary Perpetual Succour, J; Jayasimman, L (International Journal of Computer Sciences and Engineering, 2025)
This paper discusses the application of multimedia technologies in web learning environment. It presents the suitable classification algorithm based on regression analysis to predict the learners’ needs and performance. Predicting educational outcome and monitoring the progress of students in a web-based learning setting is a difficult task. But, there are possibilities to improve the system based on individual learning pattern in the web learning environment. In this paper, regression algorithm is implemented to predict student performance at the end of the semester. The results can be used to improve the educators’ perception to reform the syllabus, thereby escalating the probability of a higher score by covering students. Higher learning institutes contribution reserve learning courses during the web can use this replica to identify which area of their itinerary can be improved by data mining technology to accomplish and enhance the performance of the student. By attempting to study the new algorithm this, research paper is a need of the hour. The main aim of this research paper is to study about the newly proposed regression algorithm and its’ efficiency. It discusses the multimedia elements and their effects in the web learning system.